2017
DOI: 10.18632/genesandcancer.145
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of erlotinib, carboplatin, pemetrexed, and bevacizumab in chemotherapy-naïve patients with advanced non-squamous non-small cell lung cancer harboring epidermal growth factor receptor mutation

Abstract: Background Epidermal growth factor receptor tyrosine kinase inhibitors significantly prolong the progression-free survival of patients with non-squamous non-small cell lung cancer (NSCLC). However, most patients develop tumor regrowth and their prognosis remains poor. A new treatment strategy for NSCLC harboring EGFR mutation is therefore necessary. Methods In phase I, eligible patients were administered oral erlotinib daily and intravenous pemetrexed, carboplatin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…Our research found that the EGFR mutation-positive stage IIIA NSCLC patients are extremely sensitive to the NTT strategy, meanwhile, the incidence of grade 3/4 AEs in the NTT group was significantly lower than that of NCT. Consistent with previous reported results, the main adverse event of NTT is skin rash, and the main adverse events of NCT are myelosuppression and gastrointestinal reaction ( 22 ). In clinical practice, the toxicity associated with myelosuppression may be ignored by patients because it has no direct symptoms in the early stage ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our research found that the EGFR mutation-positive stage IIIA NSCLC patients are extremely sensitive to the NTT strategy, meanwhile, the incidence of grade 3/4 AEs in the NTT group was significantly lower than that of NCT. Consistent with previous reported results, the main adverse event of NTT is skin rash, and the main adverse events of NCT are myelosuppression and gastrointestinal reaction ( 22 ). In clinical practice, the toxicity associated with myelosuppression may be ignored by patients because it has no direct symptoms in the early stage ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, despite achieving significant downstaging of tumors, local or distant disease relapsed in less than 1 year. Various combination therapy achieved the promising results in the setting of advanced stage, including chemotherapy/EGFR-TKI ( 3 , 4 ), chemotherapy/Bevacizumab ( 5 ), EGFR-TKI/Bevacizumab ( 6 , 7 ), and eventually chemotherapy/EGFR-TKI/Bevacizumab ( 8 ). Currently, some prospective trials ( 9 11 ) had investigated the critical role of EGFR-TKI (gefitinib or erlotinib) in neoadjuvant therapy, the objective response rate (ORR) was ranged from 42.1 to 54.5%, and the rate of major pathological regression (MPR) was from 9.7% up to 24.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first- and second- generation EGFR TKIs are active for EGFR C797S and SM, the patient inevitably undergo development of the EGFR SM/C797S/T790M triple mutations [18] . Now, the promising results of various combination therapy are coming out, including TKI plus chemotherapy, [19,20] TKI plus bevacizumab, [10] bevacizumab plus chemotherapy, [21] and eventually TKI plus bevacizumab and chemotherapy [22] . A neoadjuvant 4-agent combination therapy, icotinib plus carboplatin, pemetrexed and bevacizumab, for locally advanced non-squamous NSCLC patient harboring EGFR mutations avoiding total pneumonectomy were reported [23] .…”
Section: Discussionmentioning
confidence: 99%